Penerapan Inovasi Pelayanan PubliK GO-DOK Di Kota Tasikmalaya - Pirman Maolana; Tania Firda Anggraini Maruao; Asri Hidayani; Cepi Sandra Wijaya; Fikri Ardiansyah (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2020)
Demands for public service innovation are increasingly pressing along with the increasing awareness that the community has the right to be served and the government has an obligation to provide the best service. One of the services provided by the government to the community is population administration services. In this case the researcher examines how the GO-DOK service innovation is applied. This research uses qualitative methods and descriptive approaches. This study uses public service theory and public service innovation. Determination of implementing informants using snowball sampling and user informants using purposive sampling. The latest innovation service presented by the City of Tasikmalaya government in the use of digital-based efforts to facilitate the community, especially in population administration services in the City of Tasikmalaya. With a delivery service developed by the Disdukcapil of Tasikmalaya city.